2021
DOI: 10.3390/antiox10060929
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinone Exposure Worsens Rheumatoid Arthritis through the Activation of the Aryl Hydrocarbon Receptor and Interleukin-17 Pathways

Abstract: Rheumatoid arthritis (RA) development is strongly associated with cigarette smoke exposure, which activates the aryl hydrocarbon receptor (AhR) as a trigger for Th17 inflammatory pathways. We previously demonstrated that the exposure to hydroquinone (HQ), one of the major compounds of cigarette tar, aggravates the arthritis symptomatology in rats. However, the mechanisms related to the HQ-related RA still remain elusive. Cell viability, cytokine secretion, and gene expression were measured in RA human fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…The four complex compounds were synthesized: (1) 1). The complexes (1)-( 3) are known in the literature [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The four complex compounds were synthesized: (1) 1). The complexes (1)-( 3) are known in the literature [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The human body has many defense mechanisms that neutralize the harmful effects of reactive oxygen species. Antioxidants play an important role in reducing oxidative damage in the human body [1][2][3][4][5]. These are compounds which, even at a very low concentration, compared to the substrate, can delay or prevent its oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as HQ can induce the generation of ROS in different biological systems (Heluany et al, 2018b; Heluany et al, 2021; Mao et al, 2019), and the induction of oxidative stress in chondrocytes has been strongly associated with cartilage damage in OA (Henrotin, Bruckner and Pujol, 2003), we tested whether the HQ exposure could influence the production of ROS in BACs cultures. Our data showed that an incubation of chondrocytes with HQ for 24 hours triggered a significant increase in the levels of ROS in comparison to non-stimulated cells (Figure 2I).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that exposure to HQ aggravated joint damage in experimental animal models of rheumatoid arthritis (RA) through the activation of the aryl hydrocarbon receptor (AhR) pathway by promoting inflammation, an increased influx of immune cells, synovial proliferation and oxidative stress (Heluany et al, 2018a,b; Heluany et al, 2021).…”
Section: Introductionmentioning
confidence: 99%